The phagosome containing Legionella pneumophila within the protozoan Hartmannella vermiformis is surrounded by the rough endoplasmic reticulum. - Abu Kwaik, Y (1996)
Legionella pneumophila is an intracellular parasite of protozoa and human phagocytes. To examine adaptation of this bacterium to parasitize protozoa, the sequence of events of the intracellular infection of the amoeba Hartmannella vermiformis was examined. The previously described uptake phenomenon of coiling phagocytosis by human monocytes was not detected. A 1 h postinfection with wild-type strain AA100, mitochondria were observed within the vicinity of the phagosome. At 2.5 h postinfection, numerous vesicles surrounded the phagosomes and mitochondria were in close proximity to the phagosome. At 5 h postinfection, the bacterium was surrounded by a ribosome-studded multilayer membrane. Bacterial multiplication was evident by 8 h postinfection, and the phagosome was surrounded by a ribosome-studded multilayer membrane until 15 h postinfection. The recruitment of organelles and formation of the ribosome-studded phagosome was defective in an isogenic attenuated mutant of L. pneumophila (strain AA101A) that failed to replicate within amoebae. At 20 h postinfection with wild-type strain AA100, numerous bacteria were present in the phagosome and ribosome were not detected around the phagosome. These data showed that, at the ultrastructural level, the intracellular infection of protozoa by L. pneumophila is highly similar to that of infection of macrophages. Immunocytochemical studies provided evidence that at 5 h postinfection the phagosome containing L. pneumophila acquired an abundant amount of the endoplasmic reticulum-specific protein (BiP). Similar to phagosomes containing heat-killed wild-type L. pneumophila, the BiP protein was not detectable in phagosomes containing the mutant strain AA101A. In addition to the absence of ribosomes and mitochondria, the BiP protein was not detected in the phagosomes at 20 h postinfection with wild-type L. pneumophila. The data indicated that the ability of L. pneumophila to establish the intracellular infection of amoebae is dependent on its capacity to reside and multiply within a phagosome surrounded by the rough endoplasmic reticulum. This compartment may constitute a rich source of nutrients for the bacteria and is probably recognized as cellular compartment. The remarkable similarity of the intracellular infections of macrophages and protozoa by L. pneumophila strongly supports the hypothesis that adaptation of the bacterium to the intracellular environment of protozoa may be the mechanism for its ability to adapt to the intracellular environment of human alveolar macrophages and causes pneumonia.